Increasing Higher Order Thinking Skills of Elementary School Students Through Video in Environmental Pollution Case - Musyaffa, AA; Asiah, Siti (Universitas Pahlawan Tuanku Tambusai, 2022)
The research was carried out on the science learning process on environmental material is one of the important topic. Students at the elementary school level have an important role play a role in protecting the environment around them. This research is carried out with the aim of improving Higher Order Thinking Skills (HOTS) students in learning science on environmental materials. as for The research method used in this study uses Classroom Action Research with details of 3 cycles. The research was conducted during September-0ktober 2021 at SDN 054/IV and SDN 048/IV . The number of samples taken is 76 students. this research the treatment given is to play case-based learning videos in class.The results showed that there was an increase in students' HOTS in science subjects learning using case-based videos. The conclusion of this study is that case-based learning video can increase the HOTS of SDN students in the Teluk Teluk Subdistrict, Jambi City.